If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -14 = 46 Reorder the terms: -14 + 6x = 46 Solving -14 + 6x = 46 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 6x = 46 + 14 Combine like terms: -14 + 14 = 0 0 + 6x = 46 + 14 6x = 46 + 14 Combine like terms: 46 + 14 = 60 6x = 60 Divide each side by '6'. x = 10 Simplifying x = 10
| 3n-6n=9 | | 2(4x+5)-3x=24-2x | | (3m+4)(6m+m-2)=0 | | 4h+32=60 | | 4x(3x^2-7x-16)= | | x^2+70x-144=0 | | 10+3(5x-2)=7(2x-1)+9 | | t(3t-20)=-12 | | 14y=-34 | | 4x(2x+3)=36 | | 7y^2-16y-28=0 | | 13m=5 | | 48x^2+14-45=0 | | 48x^2+14=45 | | 4x^2=28x-49 | | 1+8x=11-2x | | 10y^2=-5y | | 4x+2x=-30 | | 6(x-1)-(x-2)=-18 | | -17-5x=13-8x | | 5x^2+18x=-32-8x | | t^2=9t | | 3.5x-4=2.5x | | 14x^2+51x=54 | | 28(a-2)+21=12a+61 | | x^3+8x=-6x^2 | | 36x^2+60x=-25 | | 7x+2=6x | | 65=3x-5 | | -6x+14=7x-12 | | (3n-12)=6 | | y=(x+6)(x-7) |